2020
DOI: 10.1186/s13643-020-01518-z
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative prognostic factors associated with postoperative delirium in older people undergoing surgery: protocol for a systematic review and individual patient data meta-analysis

Abstract: Background Early identification of patients at risk for postoperative delirium is essential because adequate well-timed interventions could reduce the occurrence of delirium and the related detrimental outcomes. Methods We will conduct a systematic review and individual patient data (IPD) meta-analysis of prognostic studies evaluating the predictive value of risk factors associated with an increased risk of postoperative delirium in elderly patients undergoing elective surgery. We will identify eligible studi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…An experienced librarian refined the searches for individual databases. Our search strategy is available in our published protocol …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…An experienced librarian refined the searches for individual databases. Our search strategy is available in our published protocol …”
Section: Methodsmentioning
confidence: 99%
“…Details of our eligibility criteria and study selection process are provided in our published protocol. 22 In brief, we included studies that (1) enrolled adults (>16 years) undergoing noncardiac surgery, (2) assessed perioperative factors associated with delirium, and (3) assessed delirium (up to 10 days after surgery) using the Diagnostic and Statistical Manual of Mental Disorders (Third Edition),…”
Section: Study Selectionmentioning
confidence: 99%
“…A major obstacle to the creation of a suitable algorithm is the underdiagnosis of delirium; previous studies have shown that up to two-thirds of cases are missed by healthcare professionals caring for the patient [ 13–16 ], thereby making conventional hospital records unreliable for the creation of a risk prediction model. Hence, a systematic review and meta-analysis of risk factor studies with an outcome of POD (see protocol [ 17 ]) was conducted. Included studies assessed risk factors preoperatively and systematically assessed all patients for POD for at least the first 2 days post-surgery using a validated delirium diagnosis tool.…”
Section: Methodsmentioning
confidence: 99%
“…As a common postoperative complication, all age groups of patients can affect by this complication, but this postoperative complication is highly affected geriatric patients, with an incidence rate ranging from 5% to 52% depending on the risk to patients and surgical procedure of an elderly population which often began in the post-anesthesia care unit and continuous up to 5 days post-surgical procedure. 3 , 4 …”
Section: Introductionmentioning
confidence: 99%
“…The most common complication of geriatric surgery is POD with an overall incidence rate of 5% to 52% of the geriatric surgical patient. 3 , 4 , 10 According to a recent review study, the prevalence of mortality from patients with POD was 25%. 12 This indicates that POD has a huge burden on the health-care system and the patients.…”
Section: Introductionmentioning
confidence: 99%